Manajemen Qur’ani mengatur Waktu dengan Optimal - Khaerul Kahfi; Masyhuri Rifa’i; Irdawati Saputri; Abdul Gaffar; Rini Harjanti Poapa (Gunung Djati Conference Series, 2022)
This study aims to discuss the management of Qur'anic time management optimally. This study uses a descriptive-analytical qualitative approach. The object of study in this study is the verses of the Qur'an with data collection carried out using library research. The results of this study indicate that management is managing, managing, managing or implementing while the word time in the Qur'an can be separated into four parts al-Ajal, dahr, al-Waqt and oath. Time can be implemented if someone is consistent with the plans he has made himself, so that there is no overlap in the implementation of one activity.